Brand Silence in Protest Movements: Commercial Brands’ Discursive Indifference during a Social Protest in Peru - Yalán Dongo, Eduardo (2024)
The study aims to politically analyze the narrative traits of protesting the indifference of commercial brands toward Peru’s political mobilization in November 2020 via Facebook. From a multiple-case qualitative focus, the corpus was gathered through the semiotic pertinence of representation by the isotopic saturation. The object of the study comprises 110 comments from protesters posted on the public profiles of brands that did not participate in the political protest. The pertinence of their election corresponded to the level of affinity and affection Peruvian consumers had with the brands. Based on the post-Greimasian theory, we have identified four narrative traits of protesting—exclaiming, complaining, repudiating, and wavering—over the brands. Consequently, data showed that consumers exclaimed against “their” brand, complained about the brand, repudiated the institution, and wavered over institutionality (something undefined). We identified three forms of dissemination: i) those enunciated from the Self and concerning the brands, (ii) those enunciated toward the brands, and (iii) those enunciated toward the collective self, concerning the brands. This study seeks to contribute to the literature about the narrative relationship between political consumers and brands, protests and consumption, and corporate crisis management. © 2024 Karadeniz Technical University. All rights reserved.